Whale song shows language-like statistical structure - Arnon, Inbal; Kirby, Simon; Allen, Jenny A.; Garrigue, Claire; Carroll, Emma L.; Garland, Ellen Clare (Science, 2025)
Funding: Surveys of humpback whales in New Caledonia were made possible by contributions from Fondation d’Entreprise Total and Total Pacifique; the Provinces Sud, North, and Isles; and the Ministère de la Transition Ecologique et Solidaire. This work was funded by the following grants to E.C.G: Royal Society University Research Fellowship (UF160081 and URF\R\221020), Royal Society Research Fellows Enhancement Award (RGF\EA\180213), Royal Society Research Grants for Research Fellows 2018 (RGF\R1\181014), National Geographic Grant (NGS-50654R-18), Carnegie Trust Research Incentive Grant (RIG007772), British Ecological Society Small Research Grant(SR18/1288), and School of Biology Research Committee funding. E.L.C. was supported by a Rutherford Discovery Fellowship from the Royal Society of New Zealand Te Aparangi. J.A.A. was supported by a National Science Foundation Office of Polar Programs Postdoctoral Fellowship (2218949) and a grant from the Winifred Violet Scott Trust. I.A. was supported by an Israeli Science Foundation Grant (ISF 445/20). I.A. and S.K. were supported by a fellowship from the Israel Institute for Advanced Studies. Humpback whale song is a culturally transmitted behavior. Human language, which is also culturally transmitted, has statistically coherent parts whose frequency distribution follows a power law. These properties facilitate learning, and may therefore arise because of their contribution to the faithful transmission of language over multiple cultural generations. If so, we would expect to find them in other culturally transmitted systems. Here, we apply methods based on infant speech segmentation to eight years of humpback recordings, uncovering the same statistical structure that is a hallmark of human language in whale song. This commonality, in two evolutionarily distant species, points to the role of learning and cultural transmission in the emergence of properties thought to be unique to human language. Peer reviewed